New donor–acceptor conjugates based on a trifluorenylporphyrin linked to a redox–switchable ruthenium unit12. Issue 20 (28th May 2015) - Merhi, Areej; Zhang, Xu; Yao, Dandan; Drouet, Samuel; Mongin, Olivier; Paul, Frédéric; Williams, J. A. Gareth; Fox, Mark A.; Paul-Roth, Christine O.
<x xml:space="preserve">Abstract</x> Spectroelectrochemical studies show four accessible redox states on dyad 3 with the first oxidation process taking place at the Ru(ii) centre and the second oxidation and first reduction processes at the porphyrin centre.